Efficient soft x-ray high-order harmonic generation via dual-pulse driving lasers in the overdriven regime. (20th April 2021) - Shao, Renzhi; Zhai, Chunyang; Zhang, Yinfu; He, Lixin; Zhu, Xiaosong; Lan, Pengfei; Lu, Peixiang
Abstract: We theoretically investigate the high-order harmonic generation (HHG) driven by dual-pulse lasers. The first pulse of 800 nm can create plasma in the high-density gas target. Then, the second pulse of 1800 nm is spatiotemporally reshaped by the plasma and generates soft x-ray high-order harmonics in the overdriven regime. The simulation results show that adding the first pulse can promote the phase matching of HHG in the cutoff region. As a result, a cutoff-extended HHG is achieved, which is one order of magnitude more intense than that in one pulse scheme reported previously. In dual-pulse driving lasers, the harmonic yield and the cutoff photon energy can be optimized effectively by increasing the gas pressure inside the water window region.